DEEP LITHOSPHERIC STRUCTURE AND SEISMISITY OF THE BELARUSIAN-BALTIC REGION - R. E. Girin (Геодинамика и тектонофизика)
The territory of the Belarusian-Baltic region, located in the west of the East European craton, has been represented by a three-dimensional block model showing a regular decrease in the average consolidated crustal thickness of the blocks from 59 to 39 km, in the average longitudinal wave velocity from 6.80 to 6.50 km/s, and in the lower crustal magnetization from 4–5 to 0.5 A/m. A comparative analysis of the 3D model of the deep lithospheric structure and epicentral distribution of 67 significant local tectonic events of the Belarusian-Baltic region for the period 1602–2008 showed that the Baltic part of this region experienced 6.33 times as much earthquakes and 6.76 times as much total energy release than the Belarusian part of it: 58 earthquakes and the total seismic energy release equal to 1.0399·1013 J against 9 events and 1.5382·1012 J. The vast majority of the earthquake epicenters fall within the different-type crustal block boundary zones, with the maximum number of earthquakes of the Baltic part of the region (27) occurred at the boundaries between the thickest and most solid Incukalns block of the Earth’s crust (average thickness – 59 km. average longitudinal wave velocity – 6.80 km/s) and adjacent thinner and less solid crustal blocks. The earthquake epicenters of the Baltic part of the region are largely concentrated on the Baltic Sea coast. It has been found that during the first three days after the 28.12.1908 Messina 7.1 magnitude earthquake, largest in Europe, the Belarusian-Baltic region was hit by nine significant 3.8416·1012 J total seismic energy earthquakes, which corresponds to 32 % of the whole seismic energy released therein over a 400 year period. Substantiation has been provided for the initiation of the East Baltic rift system of triple junction, its sufficient plume energy supply, which causes high seismic activity of the Baltic part of the study region. A combination of vertical and horizontal forces acting at the crustal blocks of the Belarusian-Baltic region determines the oblique-slip earthquake focal mechanism in the brittle upper consolidated crust.